INNOVATIVE FINANCIAL STRATEGIES IN LAND USE: THE ROLE AND IMPACT OF BLOCKCHAIN TECHNOLOGY (World of finance, 2024)
Introduction. In today’s rapidly evolving world the land use sector faces numerous challenges, including the need to adapt to rapidly changing economic conditions, integrate innovative technologies, and ensure transparency, efficiency, and sustainability in land resource management processes. Globalization and the development of information technologies impose new requirements on land use management, particularly regarding minimizing the risks of non-transparency, bureaucracy, and financial misconduct inherent in traditional methods. In this context, blockchain technology, known for its role in the world of cryptocurrencies, emerges as a promising tool for transforming financial strategies in land use, offering fundamentally new approaches to development, transparency, and security.Objective. To study the opportunities and impact of blockchain technology on the development of innovative financial strategies in land use.Results. The analysis of the study showed that the application of distributed ledger technologies in land use provides significant opportunities to increase transparency, efficiency, and security in land resource management. The use of such approaches contributes to process automation, reduction of administrative costs, and ensuring the accuracy of land registry data. The study also revealed that the integration of decentralized registries with other modern technologies opens up new opportunities for the development of smart city concepts and sustainable land use. However, at the same time, challenges were identified related to technical limitations, the need for changes in the regulatory environment, and the need to increase the level of trust and understanding of the technology among all participants in the process. Considering these results, it can be concluded that although distributed ledger technologies have significant potential for transforming the land use sector, their effective implementation requires a comprehensive approach and further research.Perspectives. The application of blockchain in land use is promising. This technology paves the way for the creation of innovative financial strategies that can radically transform land resource management. Firstly, the tokenization of land assets allows the conversion of property rights into digital tokens, providing greater liquidity and attracting new investors. Secondly, smart contracts automate land transaction processes, increasing efficiency and reducing the risk of errors. Moreover, blockchain creates new opportunities for project financing through crowdfunding, peer-to-peer lending, and provides transparent systems for trading land assets. Integration with other technologies, such as the Internet of Things and Artificial Intelligence, opens up prospects for the development of “smart city” concepts and sustainable land use. However, to fully realize this potential, changes in the regulatory environment, overcoming technical limitations, and increasing the level of trust and awareness among all participants in the process are necessary.